A rheological study of polymer using precipitation inhibitor, alkali, and surfactant for high salinity in carbonate reservoirs - Kalwar, S.A. (Taylor and Francis Inc., 2014)
In the present study, a new chemical formulation is designed by combining acrylic acid with the conventional alkali-surfactant-polymer (ASP) components. Acrylic acid generates precipitation inhibitor that dissolves insoluble salts. The salts known as precipitations are formed by the reaction of added chemicals with carbonate reservoir minerals or brine compositions. Various fluid-fluid compatibility tests were first performed to find an optimum acid-alkali ratio to keep ASP solutions without any precipitations for 30 days at 80°C. Using the optimum ratio, a comprehensive study was conducted to investigate the impact of acid, acid-alkali, and acid-alkali-surfactant on the viscosity of copolymer. The optimum acid-alkali ratio was found 0.6:1.0. It was observed that blend of acid with ASP solutions did not cause significant impact on the polymer viscosity. This new chemical combination provided sufficient viscosity for mobility control in the hard brine environment. Hence, the main feature of this work is the development of acid-ASP formulation, which can be more feasible for enhanced oil recovery in carbonate reservoirs as compared to conventional ASP. © 2014 Copyright © Taylor & Francis Group, LLC.